Epidemiology and medical practice - Ricardo Bruno Mendes Gonçalves (Salud Colectiva, 2022)
In this unpublished work by Ricardo Bruno Mendes Gonçalves, a key figure in the field of collective health, the relationship between epidemiology and medical practice is considered. The text is based on an inaugural lecture delivered on December 16, 1988 as part of a seminar called “Clinical epidemiology: possible scientific field or new medical ideology?” organized by the Department of Preventive Medicine at the Federal University of Bahia School of Medicine, Brazil. This manually transcribed version of the lecture was prepared, revised, and in many cases rewritten by Naomar de Almeida Filho and Jose Ricardo Ayres, who always sought to preserve the original meaning and colloquial tone that was characteristic of his lectures.